Efficient Crystal Plasticity Modeling of Lath Martensite Considering Block Boundary Effects - Sally Issa; Håkan Hallberg; Mathias Wallin; Matti Ristinmaa (Metals)
An efficient extension of conventional rate-dependent crystal plasticity is formulated to include the influence of block boundaries in lath martensite. It is shown that this can be achieved by minor modifications to a conventional crystal plasticity model, providing an efficient modeling approach with a negligible additional computational cost. With this modification, the parameter related to lattice friction is made dependent on a Hall–Petch-type block size dependency, resulting in block strengthening. The boundaries are modeled as obstacles which restrict the motion of dislocations, resulting in lower slip activity and promoting dislocation accumulation close to the boundaries. The model is calibrated and validated using experimental data from the literature, and its capabilities are demonstrated in a series of simulation examples.